Lack of ABCG2 Leads to Biventricular Dysfunction and Remodeling in Response to Hypoxia - Nagy, Bence M.; Nagaraj, Chandran; Egemnazarov, Bakytbek; Kwapiszewska, Grazyna; Stauber, Rudolf E.; Avian, Alexander; Olschewski, Horst; Olschewski, Andrea (Frontiers in Physiology, 2017)
Aims: The ATP-binding cassette (ABC)G2 transporter protects the heart from pressure overload-induced ventricular dysfunction but also protects cancer cells from chemotherapeutic agents. It is upregulated in the myocardium of heart failure patients and clears hypoxia-induced intracellular metabolites. This study employs ABCG2 knockout (KO) mice to elucidate the relevance of ABCG2 for cardiac and pulmonary vascular structure and function in chronic hypoxia, and uses human primary cardiac fibroblasts to investigate the potential role of ABCG2 in cardiac fibrosis. Methods and results: ABCG2 KO and control mice (n=10) were subjected to 4 weeks normoxia or hypoxia. This allowed for investigation of the interaction between genotype and hypoxia (GxH). In hypoxia, KO mice showed pronounced right (RV) and left (LV) ventricular diastolic dysfunction. Compared to normoxia, end-diastolic pressure (EDP) was increased in control vs. KO mice by +1.1±0.3mmHg vs. +4.8±0.3mmHg, p for GxH<0.001 (RV) and +3.9±0.5mmHg vs. +11.5±1.6mmHg, p for GxH=0.110 (LV). The same applied for myocardial fibrosis with +0.3±0.1% vs. 1.3±0.2%, p for GxH=0.036 (RV) and +0.06±0.03% vs. +0.36±0.08%, p for GxH=0.002 (LV), whereas systolic function and capillary density was unaffected. ABCG2 deficiency did not influence hypoxia-induced pulmonary hypertension or vascular remodelling. In line with these observations, human cardiac fibroblasts showed increased collagen production upon ABCG2 silencing in hypoxia (p for GxH=0.04). Conclusion: Here we provide evidence for the first time that ABCG2 membrane transporter can play a crucial role in ventricular dysfunction and fibrosis in hypoxia-induced pulmonary hypertension.